A SYSTEMATIC LITERATURE REVIEW OF THE IMPLEMENTATION OF THE SCHOOL LITERACY MOVEMENT (SLM) IN HISTORY LEARNING IN SENIOR HIGH SCHOOLS BASED ON THE PRISMA MODEL - Pratomo Yugo; Indah Wahyu Puji Utami; Ronal Ridhoi (JURNAL HISTORICA, 2025)
As part of the implementation of the Minister of Education and Culture Regulation Number 23 of 2015 concerning Character Development, a program known as the school literacy movement (SLM) was designed. This research focuses on the application of the SLM to History subjects in senior high school. The primary purpose of this research is to comprehensively map, synthesize, and critically evaluate the existing body of scholarly literature on the implementation of the SLM within history learning in senior high schools. It aims to provide a state-of-the-art overview of what is known, what is effective, and what remains unknown or challenging. This research method uses a literature study method using the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) model. This model comprises three stages such as article identification, filtering, and analysis. An analysis of the data used includes the findings, methodologies, and characteristics of the articles that passed the PRISMA model screening process. This analysis covers the nature, scope, and content of the studies that form the evidence base for the review. The results of the research show that the school literacy movement, based on analysis of the findings of the articles that have been collected, can have the potential to improve reading skills and understanding of history among students.